Proposição de um modelo para análise de fluxo de carga, curto-circuito e simulação de relés de produção - Oliveira, Arrhenius Vinícius da Costa (2004)
The objective of the present work is develop a model to simulate electrical energy networks in transient and stead states, using the software ATP (Alternative Transient Program), able to be a way to join two distinct themes, present in classical methodology planning networks: short circuit analysis and load flow theory. Beyond that, using a tool for relay simulation, this paper intend to use the new developed model to investigate the influence of transient phenomenon in operation of protection relays, and calibrate the enterprise's protections relays. For testing the model, some relays, actually, installed at COSERN were used